Recommandations linguistiques et habitudes langagières et protocolaires à l’usage des Europén.ne.s (ou d’usage uniquement en Europe ?). Écart entre la norme écrite et la norme en usage. Étude de cas : Glossaire du langage « sensible » pour la communication interne et externe (PE, 2020)/Recommendations regarding the Linguistic Practice and Behavior in (only?) European Societies. A Gap between the Written Standard and the Spoken Varieties. Case Study: French and Romanian Version of the Glossary of Sensitive Language for Internal and External Communications (PE, 2020) - Georgiana I. Badea (Editura Universității „Alexandru Ioan Cuza” din Iași, 2021)
This paper deals with political (in)correctness in translation. The primary purpose of our paper is to emphasize the politically correct notions recommended or contraindicated in the Glossary of Sensitive Language for Internal and External Communications (PE, 2020). We examine the equivalence of official versions into French and Romanian in order to understand how words that have become politically correct are substituted by politically in.correct notions.